2019
DOI: 10.1038/s41562-018-0504-3
|View full text |Cite|
|
Sign up to set email alerts
|

Positive memory specificity is associated with reduced vulnerability to depression

Abstract: Depression is the leading cause of disability worldwide 1. Early life stress exposure increases risk for depression 2 , and has been proposed to sensitise the maturing psychophysiological stress

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 74 publications
2
39
0
Order By: Relevance
“…negative) events have distal effects. In the same paper, we found that individuals with greater positive memory specificity experienced fewer negative self-cognitions, which in turn led to fewer depressive symptoms [165]. In other work, we demonstrated that children who experienced greater childhood adversity showed greater depressive symptoms 3 years later, in part due to the mediating mechanism whereby greater CM negatively affected both friendships and family support in the intervening years Fig.…”
Section: The Longitudinal Dynamics Of Resiliencesupporting
confidence: 68%
See 3 more Smart Citations
“…negative) events have distal effects. In the same paper, we found that individuals with greater positive memory specificity experienced fewer negative self-cognitions, which in turn led to fewer depressive symptoms [165]. In other work, we demonstrated that children who experienced greater childhood adversity showed greater depressive symptoms 3 years later, in part due to the mediating mechanism whereby greater CM negatively affected both friendships and family support in the intervening years Fig.…”
Section: The Longitudinal Dynamics Of Resiliencesupporting
confidence: 68%
“…Moderators directly affect the strength of the relationship between some form of adversity and an outcome, providing either a buffering or an amplifying effect. For instance, we observed that individuals who experienced more negative life events showed a stronger association between their positive memory specificity and negative self-cognitions [165]. In other words, individuals who had access to more specific positive memories displayed resilience against negative self-cognitions after negative life events.…”
Section: The Longitudinal Dynamics Of Resiliencementioning
confidence: 72%
See 2 more Smart Citations
“…Predictors of resilience in quantitative prospective-longitudinal studies include good reactivity of the hypothalamus-pituitary-adrenal gland (HPA) axis to stressors, a heterozygous catechol-o-methyl transferase (COMT) genotype, appraisal styles such as a tendency to positively reappraise and to not catastrophize about stressors, or a tendency for self-enhancement, the ability to recall specific positive memories, and strong familial and/or social support (Askelund, Schweizer, Goodyer, & Harmelen, 2019;Kalisch et al, 2017). Each single of these predisposing factors may only have a very small effect on resilient outcomes, and it has been noted that replications of significant findings in independent samples are largely absent (Bonanno et al, 2015;Kalisch et al, 2017).…”
Section: Resilience Factors As Additional Network Nodes: Hybrid Symptmentioning
confidence: 99%